2020
DOI: 10.1101/2020.10.30.362137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic doses of paracetamol with co-administration of cysteine and mannitol during early development result in long term behavioral changes in laboratory rats

Abstract: Based on several lines of evidence, numerous investigators have suggested that paracetamol exposure during early development can induce neurological disorders. We had previously postulated that paracetamol exposure early in life, if combined with antioxidants that prevent accumulation of NAPQI, the toxic metabolite of paracetamol, might be innocuous. In this study, we administered paracetamol at or below the currently recommended therapeutic dose to male laboratory rat pups aged 4-10 days. The antioxidants cys… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This case-controlled, survey-based study raised substantial concerns, as mentioned in the Introduction. Further, studies in animal models evaluating the issue have been conducted [19][20][21]36], all indicating that the drug is not safe for neurodevelopment despite a wide range of study designs. In addition, as described in the Introduction, at least 14 cohort analyses [5][6][7][8][9][10][11][12][13][14][15][16][17][18] have indicated that exposure to paracetamol during pregnancy is not safe for neurodevelopment of the fetus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This case-controlled, survey-based study raised substantial concerns, as mentioned in the Introduction. Further, studies in animal models evaluating the issue have been conducted [19][20][21]36], all indicating that the drug is not safe for neurodevelopment despite a wide range of study designs. In addition, as described in the Introduction, at least 14 cohort analyses [5][6][7][8][9][10][11][12][13][14][15][16][17][18] have indicated that exposure to paracetamol during pregnancy is not safe for neurodevelopment of the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Since this antidote is not present in the commonly used oral formulation, the University of Oulu study, even if it had been much larger and controlled for drug exposure over a period of years, would still not apply to most cases of paracetamol use. It should be noted that, in laboratory animals, exposure during the postpartum period to currently accepted levels of the intravenous formulation of paracetamol with the antidote present causes dramatic increases in asocial behavior later in life [36]. Thus, the argument is not that use of paracetamol with the antidote is safe, but rather that, hypothetically, some of the more serious adverse effects might be prevented by inclusion of the antidote with the drug.…”
Section: Discussionmentioning
confidence: 99%